Effect of vitamin c consumption toward sports performance among Malaysia elite football players / Nur Fadhle Ismail - Ismail, Nur Fadhle (Faculty of Sport Science and Recreation, 2016)
The purpose of this study is to investigate the effectiveness of vitamin C consumption in aerobic capacity, anaerobic capacity and body fat percentage among Malaysia elite football players in six weeks intervention. This study used purposive sampling where all the subjects for this study were from FELCRA FC and UKM FC. The total subjects participated in this study were 36 (N=36) subjects where 18 subject from FELCRA FC and another 18 subjects from UKM FC. Both teams were separated into groups which was FELCRA FC (experimental) and UKM FC (control). The experimental group received 1000mg of vitamin C tablet everyday while the control group received no treatment of any supplements during six weeks intervention. Result - showed that there is a significance difference (p<O.05) in body fat percentage for both experimental (p=O.OI) group and control (p=O.OI) group. In the anaerobic capacity and aerobic capacity, result for both groups showed that there is no significant difference (p>O.05). As conclusion, the findings in this study indicated that the lOOOmg of vitamin C consumption among Malaysia elite football players did not show any significant improvements in aerobic and anaerobic capacity after six weeks of intervention. However, after six weeks of 1000mg vitamin C consumption, there was an improvement of body fat where the further observation is required